2012
DOI: 10.1603/en12150
|View full text |Cite
|
Sign up to set email alerts
|

<I>Rag1</I> Aphid Resistant Soybeans Alter the Movement and Distribution of Soybean Aphid (Hemiptera: Aphididae)

Abstract: Herbivorous insects often move and distribute according to the quality of the plant they are on, and this behavior could influence interactions with plants bred for herbivore resistance. However, when an insect is normally considered sedentary, less is known about the potential importance of movement. We performed experiments to determine if a resistant soybean variety alters the movement and distribution, both within and between plants, of the soybean aphid Aphis glycines Matsumura. We did this by counting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Ladybeetles are mobile predators that actively search for prey (Forbes andGratton 2011, Meisner andIves 2013), whereas soybean aphids are sap-sucking herbivores and are relatively sedentary (Whalen and Harmon 2012). Thus, while foraging ladybeetles must struggle against the forces of drag and momentum on a moving substrate (Vogel 1994:50-80, 132-155), soybean aphids remain motionless and attached to the underside of leaves by their stylet.…”
Section: Discussionmentioning
confidence: 99%
“…Ladybeetles are mobile predators that actively search for prey (Forbes andGratton 2011, Meisner andIves 2013), whereas soybean aphids are sap-sucking herbivores and are relatively sedentary (Whalen and Harmon 2012). Thus, while foraging ladybeetles must struggle against the forces of drag and momentum on a moving substrate (Vogel 1994:50-80, 132-155), soybean aphids remain motionless and attached to the underside of leaves by their stylet.…”
Section: Discussionmentioning
confidence: 99%
“…Though block refuges maximize susceptible populations in sexual systems Gould 1998, Onstad et al 2011), it reduces the HPRÐ refuge interface, potentially limiting interplant movement of avirulent biotypes. Assuming aphids can use plant bridges within and between rows (Whalen and Harmon 2012), all HPR plants could neighbor a refuge with susceptible soybean proportions as low as 20%. In Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Asexual fecundity is known to August 2014 WENGER ET AL. : A. glycines VIRULENCE MANAGEMENT be variable by Rag gene, as is the movement of avirulent aphids (Whalen and Harmon 2012). All plants within an R0S4 microcosm are susceptible, and are assumed to be of approximately equivalent suitability for feeding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This summation accounts for how many adults are on each plant and how long they lived. Previous research indicated that adult numbers on resistant and susceptible plants can differentiate over the course of hours to days (Whalen 2012). Therefore using the day 2 count allows us to take advantage of nymph data and use a time point we expect change to already be occurring.…”
Section: Effects Of Temperature and Plant Resistance On Aphid Dynamicmentioning
confidence: 99%